2018
DOI: 10.1007/s00467-018-4042-z
|View full text |Cite
|
Sign up to set email alerts
|

The role of properdin in complement-mediated renal diseases: a new player in complement-inhibiting therapy?

Abstract: Properdin is known as the only positive regulator of the complement system. Properdin promotes the activity of this defense system by stabilizing its key enzymatic complexes: the complement alternative pathway (AP) convertases. Besides, some studies have indicated a role for properdin as an initiator of complement activity. Though the AP is a powerful activation route of the complement system, it is also involved in a wide variety of autoimmune and inflammatory diseases, many of which affect the kidneys. The r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
16
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 150 publications
(279 reference statements)
0
16
1
Order By: Relevance
“…The number of patients who tested positive for autoantibodies was somewhat lower in our study, as compared with previous reports (6,20). We hypothesize that the determination of autoantibodies in some patients when they were already receiving immunosuppressive treatments could account for this discrepancy (24,25).…”
Section: Discussioncontrasting
confidence: 79%
“…The number of patients who tested positive for autoantibodies was somewhat lower in our study, as compared with previous reports (6,20). We hypothesize that the determination of autoantibodies in some patients when they were already receiving immunosuppressive treatments could account for this discrepancy (24,25).…”
Section: Discussioncontrasting
confidence: 79%
“…While the absence of Factors B or D abrogates the assembly of the convertase complexes C3bBb and C3b n Bb (Factor D cleaves Factor B to produce Bb), the absence of properdin leaves the enzyme complexes labile to decay. The therapeutic targeting of properdin in lupus nephritis would likely require vaccinations against meningococcal disease [ 39 ]. Previously, the therapeutic application of a soluble form of a complement receptor of the Immunoglobulin superfamily, which functions as an inhibitor of the alternative pathway, led to a reduction in lupus nephritis at a comparable endpoint (4 months) in MRL/ lpr mice, but, in contrast to our study, showed no effect on the levels of autoantibodies [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…The role of properdin as a pattern‐recognition molecule and initiator of the AP has been extensively discussed: it seems that binding of properdin to complement activating surfaces depends on the initial C3b deposition . As the only known positive regulator of the CS, it has not been established whether properdin plays a role in complement‐mediated renal diseases, or whether properdin could be a therapeutic target . Properdin seems to be implicated in complement‐mediated diseases, such as in renal ischemia/reperfusion injury (IRI) lesions .…”
Section: Discussionmentioning
confidence: 99%